Impact of the mother literacy, occupation and socioeconomic status on the nutritional status Of the children - Shanker, H; Hassan, M A; H, Nveen K; Dwivedi, Shraddha (Indian Journal of Community Health, 2006)
Impact of mother literacy, occupation and socioecnomic status on the nutritional status of the children. Research Question 1. What are the impact of mother's literacy on the nutrtional status of the children. 2. To study the effect of mother's occupation and socio-economic status on the nutritional status of the children? 3. To suggest the various preventive measures to combat the nutritional problems. Material and Methods a) Study Design : A stratified multistage random sampling. b) Setting : A sample of two blocks namely, Jasra in trans Jamuna area and Saidabad in trans Gangs area. c) Participants : Children below 6 years of age. d) Sample Size : 436 children below 6 years of age. e) Study Variables : Literacy, occupation and socioeconomic status. Statistical Analyses : By proportions and Chi-square test Results :The overall prevalence of malnutrition was found to be maximum in children of illiterate mother i.e 58.24 percent